Metabolic rewiring in keratinocytes by miR‐31‐5p identifies therapeutic intervention for psoriasis - Mao‐Jie Wang; Huan‐Jie Huang; Yong‐Yue Xu; Harmjan Vos; Can Gulersonmez; Edwin Stigter; Johan Gerritsen; Marc Pages Gallego; Robert van Es; Li Li; Hao Deng; Lin Han; et al. (EMBO Molecular Medicine)
Abstract Besides genetic alterations, the cellular environment also determines disease onset and progression. When different cell types contribute to disease outcome, this imposes environmental challenges as different cell types likely differ in their extracellular dependencies. Hsa‐microRNA‐31‐5p (miR‐31) is highly expressed in keratinocytes of psoriatic skin, and we show that expression in keratinocytes is induced by limited glucose availability and enables increased survival under limiting glucose conditions by increasing glutamine metabolism. In addition, miR‐31 expression results in not only secretion of specific metabolites (aspartate and glutamate) but also secretion of immunomodulatory factors. We show that this miR‐31‐induced secretory phenotype is sufficient to induce Th17 cell differentiation, a hallmark of psoriasis. Inhibitors of miR31‐induced metabolic rewiring and metabolic crosstalk with immune cells alleviate psoriasis pathology in a mouse model of psoriasis. Together our data illustrate an emerging concept of metabolic interaction across cell compartments that characterizes disease development, which can be employed to design effective treatment options for disease, as shown here for psoriasis.